Analysis Of Marketing Strategies To Increase Sales In PT. Mitra Pinasthika Mustika (MPM) Honda Motor Medan - Asido Loyandro Samosir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
Marketing strategy is aform of a plan that is broken down in the field of marketing. “Mitra Pinasthika Mustika (MPM) Honda Motor Medan”. The data collection method can be obtained by direct interviews and than a SWOT analysys is carried out by comparing the external factors of opportunities and threats with internal factors of strengths and weaknesses so that from the analysis. The internal factors is the strngth of PT. Mitra pinasthika Mustika (MPM) Honda Motor Medan is greater than the internal factor, the weakness is 0,08, and the external is the opportunity that is greator than the external factor, the threat is 0,44. So that it can be found an appropriate marketing strategy formulation by utilizing all strength to seize and take advantage of opportunities as best as posible, maintain and improve the quality of products and excellent services in the hope of being able to maintain customer. The aplication of marketyng strategy by PT. Mitra Pinasthika mustika (MPM) Honda Motor Medan is by choosing to formulate the target market by segmenting, targeting and positioning. In addition, developing a marketing system or marketing mix consisting of four main elements, namely product, price, distribution and promotion